Review the experience: role of propranolol in infantile hemangioma (IHs) on pediatric patient - More, Santosh; Budhwani, K. S.; Ghritlaharey, R. Kumar (International Surgery Journal, 2018)
Background: Although not being licensed for the treatment of infantile hemangiomas (IHs) on pediatric patient 5 weeks or older than 5 months, propranolol is often used in these age groups to prevent or to treat potentially severe complications. The objective of the present study was to review the experience on pediatric patients with efficacy and adverse effects after use of oral propranolol treatment for IHs started before 5 weeks or after 5 months of age. Methods: This was an observational study performed pediatric patients with IHs treated with oral propranolol at the department of pediatric surgery, Gandhi Medical College and Associated Kamla Nehru Hospital, Bhopal from Nov 2012-Nov 2014. Using a proforma, data was collected on dosing, efficacy and adverse effects. Results: A total 40 patient of IHs from 2 months to 3yr were included in this study. The majority of patients were ≤6month of age 24 (60%) patient and 16 (40%) patients were >6month of age. Female 28 (70%) are more affected than male 12 (30%). The IHs most common lesion was 23 (57.5%) in head, face and nose region. No adverse effects were observed in our series; none of our patients had symptoms of hypoglycemia or hypotension. The patients with clinically significant more than 50% volume reduction were found in 26 (65%) patient and 25-50% volume reduction were found 14 (35%) patient after 5months long propranolol therapy for IHs. Conclusions: In present study of patients propranolol 2mgdivided into two doses was a well-tolerated and effective treatment of IHs. Propranolol is clinically more effective treatment with no adverse effect and cost effective. The percentage of regression of size and color clearance was sufficient to justify the use of propranolol as the first line option for treatment of IHs.